Study the Effect of PH Variation on the Particle Size of Sio2 Thin Films - Dhahir, Mohamed K.; Khyoon, Hasan . A. (Iraqi Journal of Laser, 2019)
In this paper, SiO2 nanoparticles thin films were synthesised at different PH values of solution by sol gel method at fixed temperature (25oC) and molar ratio (R =H2O/precursor) of (Tetra Ethyl Ortho Silicate) TEOS as precursor at (R=1). The structure and optical properties of the thin films have been investigated. All thin films were tested by using X-RAY diffraction. All X-RAY spectrum can be indexed as monoclinic structure with strong crystalline (110) plane. The morphological properties of the prepared films were studied by SEM. The results indicate that all films are in nano scale and the particle size around (19-62) nm .The size of silica particles increases with increasing PH value of solution where both the rate of hydrolysis and condensation become faster and affect on the solubility of intermediate [Si (OC2H5)4-X(OH)X] and hence affect on the supersaturation of the nucleation process . Also the UV-visible study indicates that the absorption is minimum and transmittance is maximum at the visible range of the spectrum. Accordingly, the sample is suitable for antireflection coating such as solar cells.